2015
DOI: 10.1287/mnsc.2014.1953
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Compound Risk in Relation to Simple Risk and to Ambiguity

Abstract: We conduct experiments measuring individual behavior under compound risk, simple risk, and ambiguity. We focus on (1) treatment of compound risks relative to simple risks and (2) the relationship between compound risk attitudes and ambiguity attitudes. We find that compound risks are valued differently than corresponding reduced simple risks. These differences measure compound risk attitudes. These attitudes display more aversion as the reduced probability of the winning event increases. Like Halevy [Halevy Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 33 publications
9
80
1
Order By: Relevance
“…For recent reviews of the experimental literature see Hey (2014); Trautmann and van de Kuilen (2015) 2 Also see Abdellaoui, Klibanoff, and Placido (2015).…”
mentioning
confidence: 99%
“…For recent reviews of the experimental literature see Hey (2014); Trautmann and van de Kuilen (2015) 2 Also see Abdellaoui, Klibanoff, and Placido (2015).…”
mentioning
confidence: 99%
“…Qualitatively similar results were also obtained by Dean and Ortoleva (2015) and by Armantier and Treich (2015), who show that not only was attitude to compound risk tightly associated to attitude towards ambiguity, but so was attitude towards complex risk. 17 Abdellaoui et al (2015) also find, in a setup close to Halevy's, an association between compound risk reduction and ambiguity neutrality. The association they find is however weaker than in Halevy's data.…”
Section: Predictions and Literature Reviewmentioning
confidence: 57%
“…Although we do not explicitly test any specific theory that might explain why compound risk may be associated with ambiguity, we try to shed light on this issue through an experimental setup where the compound lottery is extremely simple. If cognitive inability is at the basis of failures to reduce compound probabilities (Abdellaoui et al, 2015;Harrison et al, 2015), and aversion to compound lottery reflects a deficiency of the 'human intuitive statistician' (Budescu and Fischer, 2001), then by designing a compound risk situation that is very easily reducible, we partly rule out instances based on limited cognitive ability, and we expect subjects to effectively reduce compound risk if the probabilities of the two layers of uncertainty are objectively given.…”
Section: Predictions and Literature Reviewmentioning
confidence: 99%
“…We suggest that this result is caused by lack of tolerance for conjunction of two types of uncertainty expressed by two different discounting processes: time discounting and uncertainty discounting. This can be considered analogous to compound risk aversion: prospects comprising more sources of uncertainty look less attractive than those comprising only one source of uncertainty (Dillenberger, 2001;Abdellaoui et al, 2015). There is also an alternative interpretation: lack of tolerance for conjunction of time discounting and uncertainty discounting could be caused by negative affect associated with the prolonged state of uncertainty -the delayed state of uncertainty could be extremely aversive.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this axiom, research shows that when choosing between equivalent lotteries people prefer one-stage over multi-stage lotteries (Budescu & Fischer, 2001;Halevy, 2007). Dillenberger (2001) and Abdellaoui, Klibanoff, and Placido (2015) even introduced the concept of compound risk aversion, meaning that the decision maker's certainty equivalent for a compound lottery is below the certainty equivalent for a simple lottery. Spears (2013) showed that some people prefer simple over compound lotteries even when the simple lotteries offer lower expected value.…”
Section: In Practice Vanderveldt Et Al Use the Formula In Equationmentioning
confidence: 99%